Analisis dan Evaluasi Desain UI/UX Website Taekwondo Valentino Club Menggunakan Pendekatan Design Thinking - Daniati Uki Eka Saputri; Taopik Hidayat; Nurul Khasanah; Faruq Aziz (Jurnal Teknologi Terpadu, 2026)
This study aims to analyze and evaluate the user interface (UI) and user experience (UX) design of the Taekwondo Valentino Club website using a Design Thinking approach. The research was conducted within a community-based sports club characterized by non-technical users and a relatively informal organizational structure. The methodology followed the five stages of Design Thinking—empathize, define, ideate, prototype, and test—with data collected through participatory observation, semi-structured interviews, and usability testing using the System Usability Scale (SUS). The study involved 41 respondents, including club administrators, coaches, and members. The evaluation results show an average SUS score of 83, placing it in the Excellent category. Overall, users did not exhibit negative perceptions regarding system complexity, consistency, or practicality. Task-based observation further indicated that the majority of respondents completed all usage scenarios without requiring additional technical assistance. The findings demonstrate that the Design Thinking approach is effective in producing an intuitive and easy-to-use UI/UX design that aligns with the needs of community sports club users. This study contributes to UI/UX research by highlighting interface requirement patterns specific to community-based sports organizations and supports ongoing efforts to digitize community sports club management.